HUMAN FACTORS STUDY OF QMC CLOTHING AND EQUIPMENT DURING COLD WEATHER TESTS OF THE SERGEANT MISSILE SYSTEM, II. - McGinnis,John M.; Zimmerer,Theodore (1962)
A previous study was based on cold weather tests of the SERGEANT Missile System which were held at the Eglin AFB Climatic Laboratory during the summer of 1959. The observations described in the present report were made in the same laboratory in 1962. Both studies are part of a continuing effort by the Quartermaster Corps to insure compatibility between the QM-equipped soldier and Army military systems which he will be required to operate. The general purpose of these studies is to detect problems associated with QMC clothing in the operation of Army equipment 9systems, and to report these problems to the responsible design and development groups. (Author)